Bridging gender gaps in political participation: Experimental evidence on group-based trainings from Nigeria - Adida, Claire; Kosec, Katrina; Kyle, Jordan; Mo, Cecilia Hyunjung; Arriola, Leonardo; Matanock, Aila; Adeyanju, Dolapo; Fisher, Rachel (International Food Policy Research Institute, 2025)
Women’s political participation remains persistently lower than men’s worldwide. While barriers to women’s civic engagement are well documented, there is limited causal evidence on how to effectively close gender gaps in participation. This study evaluates whether a group-based training intervention can enhance women’s engagement in local governance. In a randomized controlled trial across 300 communities in rural southwest Nigeria, we recruited 3,900 politically unaffiliated women into newly formed women’s action committees (WACs). Control WACs received a single civic education training, while treatment WACs received five additional trainings aimed at strengthening women’s collective efficacy over the course of six months. Leveraging baseline (May–July 2023) and endline (January—February 2024) surveys alongside behavioral data from a community grants competition, we find that the intervention significantly increased both the level and quality of women’s political participation. Treated communities also exhibited greater responsiveness by local leaders to women’s needs and priorities. These findings show that group-based interventions can meaningfully and scalably narrow gender gaps in civic participation.